2003
DOI: 10.1007/s00424-002-1003-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of constitutively expressed heme oxygenase-2 in the regulation of guinea pig coronary artery tone

Abstract: Carbon monoxide (CO) is well known as a relaxing substance in the vasculature, where it is released during the heme oxygenase (HO) reaction. Little is known about the tissue-specific targets of CO in smooth muscles. To date the functional role of CO in the coronary artery remains unclear. The expression of HO-2, the constitutive isoform of HO, but not of HO-1 (inducible HO isoform) was demonstrated by immunohistochemical reaction. Contractile studies, performed under isometrical conditions, showed that CO, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
(33 reference statements)
2
23
0
1
Order By: Relevance
“…Because CO is the active vasodilator produced by HO, we assume that this gaseous mediator is involved in dilation, although we did not measure CO production directly. A role for HO-2 in the regulation of coronary vasomotor reactions has been established in isolated coronary arteries (18). These investigators also found that CO-mediated dilation was mediated via cGMP and cGMP-dependent protein kinase modification of the K Ca channel.…”
Section: Comparisons With Literaturementioning
confidence: 93%
See 2 more Smart Citations
“…Because CO is the active vasodilator produced by HO, we assume that this gaseous mediator is involved in dilation, although we did not measure CO production directly. A role for HO-2 in the regulation of coronary vasomotor reactions has been established in isolated coronary arteries (18). These investigators also found that CO-mediated dilation was mediated via cGMP and cGMP-dependent protein kinase modification of the K Ca channel.…”
Section: Comparisons With Literaturementioning
confidence: 93%
“…CO is reported to modulate the activity of K Ca channels (47). In isolated coronary arterioles, CO produced dilation via activation of a pathway involving GC, cGMP-dependent protein kinase, and K Ca channels (18). Our protocols did not evaluate the contribution of K ϩ channels to CO-induced vasodilation in this setting, but such a contribution would have been eliminated by the KCl suffusion.…”
Section: Comparisons With Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…The BK Ca channel activity is subjected to modulation by a wide spectrum of biologically relevant factors such as Ser/Thr/Tyr phosphorylation, Cys/Met oxidation, steroid hormones, and diatomic gases (O 2 , NO, and CO) [111][112][113][114]. The PKG-dependent activation of the Na þ /Ca 2þ exchanger by CO has been proposed [12]: this may increase the submembrane Ca 2þ concentration in the vicinity of the BK Ca channels with their consequential opening [115]. An activated cGMP pathway may be permissive for BK Ca channels activation by CO [12].…”
Section: Co Signalingmentioning
confidence: 99%
“…11,41 Consistently, the suppression of the PLC-IP 3 pathway observed in our study is in agreement with reports showing the attenuation of PLC activity in isolated guinea pig coronary smooth muscle cells in vitro. 46,47 The simultaneous reduction of PLC activity, ET-1 and NFkB by an upregulated HO system will attenuate tissue inflammation. 44,45,48 This notion is consistent with previous studies in which an upregulated HO system suppressed immune/inflammatory responses by abolishing macrophage infiltration and reducing mast-cell and basophils histamine release.…”
Section: Discussionmentioning
confidence: 99%